Le BPC et les risques qu’il présente - Moreau, Rémi (Assurances, 1988)
PCB's were first introduced in Canada in 1929 and since that time have been used as component of many products. PCB's were prohibited in the United States and Canada in the seventies by many environmental legislations. But the problem is how to safely dispose of over 55 years of production. Me Rémi Moreau briefly describes in this article the properties of PCB's, the inherent risks, the direct and consequential damages, such as bodily injury, property damage, loss of income, debris removal. The author also comments on the underwriting of PCB's exposures and finally insists on a prevention program. The following insurance is discussed in regard of PCB's coverages, exclusions or limitations: automobile insurance, property insurance, boiler and machinery insurance and liability insurance.